2015
DOI: 10.1111/dpr.12096
|View full text |Cite
|
Sign up to set email alerts
|

How Traceability is Restructuring Malawi's Tobacco Industry

Abstract: 5ACknowledgements 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In addition, the leaf-buying firms provide contract farmers with extension services that require a stricter schedule to tend to the nursery as well as the process of harvesting, which according to focus group participants may result in less labour costs for nursery tasks. This finding supports one of the rationale supporting the implementation of IPS, namely to increase efficiency and compliance in tobacco production 20. The cost analysis contributes to the literature by disaggregating contract and independent farmers, as others have found that together smallholder farmers continue to face high production costs 32…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In addition, the leaf-buying firms provide contract farmers with extension services that require a stricter schedule to tend to the nursery as well as the process of harvesting, which according to focus group participants may result in less labour costs for nursery tasks. This finding supports one of the rationale supporting the implementation of IPS, namely to increase efficiency and compliance in tobacco production 20. The cost analysis contributes to the literature by disaggregating contract and independent farmers, as others have found that together smallholder farmers continue to face high production costs 32…”
Section: Discussionsupporting
confidence: 70%
“…Under significant pressure from leaf-buying firms and transnational tobacco corporations, the burley tobacco contract marketing was approved by the government and fully adopted in 2012 as the Integrated Production System (IPS). The majority of tobacco leaf produced in Malawi is now sold through contract farming 20. Many farmers have agreed to contractual arrangements because it is difficult to access other bank and government credit facilities 20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ponte and Ewert (2009) suggest a more detailed understanding of upgrading possibilities in agro-food GVCs, including processes usually considered to be downgrading in the GVC literature, e.g., selling lower value products on a larger scale [20].) Several agri-food GVC studies discuss how lead firms facilitate or restrict the prospects for upgrading farms and companies in the Global South (e.g., [9,[21][22][23][24]). Upgrading potential and limitations for smallholders and agri-food processors as a result of more demanding food safety and quality standards imposed by northern retailers have been studied extensively in Kenya (see amongst others [9,[25][26][27]).…”
Section: Conceptualising Upgrading In Global Agricultural Value Chainsmentioning
confidence: 99%
“…In Malawi, leaf merchants wish to aggressively expand contract farming due to pressure from cigarette manufacturers for full traceability, but as of July 2012 this has been resisted by government (for a full discussion, see Moyer‐Lee and Prowse ). At the national level, a complete shift to contract farming has repercussions for ancillary industries: fertilizer suppliers, transporters and commercial graders.…”
Section: The Burley Tobacco Segment In 2009/10mentioning
confidence: 99%